Work Values and Anticipatory Psychological Contract Among Final Year University Students (Annual of the Faculty of Philosophy in Skopje, 2017)
This article examines the prediction of anticipatory psychological contract components on the basis of work values among final year university students, as potential job applicants (i.e. psychological contract). Taking into consideration the goals young people tend to realize through work, on the one hand and the nature of different types of psychological contract, on the other, it was postulated that social work values will have the strongest contribution in explaining the variance in beliefs about relational employee contributions and beliefs about relational employer inducements. The strongest predictor of beliefs about transactional employee contributions and beliefs about transactional employer inducements was assumed to be utilitarian work values.The sample consisted of 312 participants, students of final year of studies in the field of natural sciences, humanities, social sciences and technical studies at the Ss. Cyril and Methodius University. Applied hierarchical multiple linear regression analysis showed that social work values were significant predictors of beliefs about relational employee contributions and beliefs about relational employer inducements, whereas utilitarian work values significantly predicted beliefs about transactional mutual obligations with the future employer. It was found that significant part of the variance in beliefs about relational and transactional employer inducement was explained by the other groups of work values.The results are discussed and their practical implications are highlighted.
Keywords: ANTICIPATORY PSYCHOLOGICAL CONTRACT; WORK VALUES; PREDICTION